O Discurso da História nas Malhas da Ficção: Netto Perde sua Alma e o Novo Conceito de Romance Histórico - Vedoin, Gilson (Revista Sociais e Humanas, 2010)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> In Netto perde sua alma (1995) Tabajara Ruas rejects the rules proposed by Walter Scott in the composition of this traditional historical novel. He writes his novel following the fictional moment that proliferated in Latin America at the end of 40’s. That play is considered as a new historical novel. This way, the mixture between fiction and history, in that romance, reveals the author’s aim, that is, to question and to rewtite, based to a new critic perspective, some traditional facts of canonic history.